Public vs Private: The Four Categories of Open-Air Spaces at the Late Minoan IIIC Middle Settlement at Monastiraki – Halasmenos (Ierapetra, Crete) - Rupp, David W. (Journal of Greek Archaeology, 2021)
On the eastern side of the Isthmus of Ierapetra (Crete), just to the north of the village of Monastiraki, and immediately to the south of the mouth of the Ha Gorge, is situated the Late Minoan IIIC (LM IIIC) settlement of Monastiraki – Halasmenos (Tsipopoulou 2011a, 323). It is one of six sites excavated in the northern part of the Isthmus (Figure 1) which were occupied at some point during the 12th century BC (Kavousi – Kastro, Kavousi – Vronda, Kavousi – Azoria, Monastiraki – Katalimata and Vasiliki – Kephala).